In vitro antioxidant activity, α-glucosidase inhibitory potential and in vivo protective effect of Asparagus stipularis Forssk aqueous extract against high-fructose diet-induced metabolic syndrome in rats. (August 2018) - Adouni, Khaoula; Zouaoui, Olfa; Chahdoura, Hassiba; Thouri, Amira; Lamine, Jihen Ben; Santos-Buelga, Celestino; González-Paramás, Ana M.; Maggi, Filippo; Mosbah, Habib; Haouas, Zohra; Neffati, Fadoua; Achour, Lotfi
Graphical abstract: Highlights: ASD showed a dose dependently antioxidant activity in all assays investigated. ASD showed 7–fold higher α-glucosidase inhibition value than acarbose. ASD possesses a protective effect against HFD-induced Met S. Abstract: The study was carried out to evaluate the in vitro antioxidant, α-glucosidase inhibitory potential and the protective effect of Asparagus stipularis Forssk aqueous extract against high-fructose diet (HFD; 10% fructose solution for 5 months) induced metabolic syndrome in rats. An A. stipularis shoots decoction (ASD) was administered orally (100 and 300 mg/kg body weight), daily for 4 weeks. Controls were performed using metformin (150 mg/kg) as a standard drug. HPLC-MS analysis showed hydroxycinnamoyl derivatives and flavonoid glycosides as the major constituents of ASD. Fructose fed rats showed hyperglycemia, dyslipidemia, impaired glucose tolerance and an increase of inflammation markers (alkaline phosphatase, aspartate transaminase and alanine transaminase) together with higher values of lipid peroxidation and lowered activities of antioxidants enzymes in liver. Hepatic histopathological examinations were performed. Variable sized fat vacuoles and diffuse lymphocytic infiltration were observed. ASD treatment prevented these abnormalities, demonstrating its protective effect against HFD-induced metabolic syndrome in rats.